Modular nine-level single-phase inverter with quadruple voltage gain using reduced blocking voltage switches - V. Fernão Pires; Armando Cordeiro; Daniel Foito; Joaquim Monteiro; Hao Chen; J. Fernando Silva (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
This paper presents a novel approach to enhancing modular voltage source inverters, focusing on achieving high-voltage gain and minimizing harmonic distortion. The suggested solution includes a transformerless, single-phase, nine-level voltage source inverter that cuts down on the number of passive parts that are needed while still achieving a high-voltage gain of up to four times the input DC voltage sources. An essential feature of this topology is that all the switches are subjected to a maximum blocking voltage four times lower than the maximum AC voltage that can be applied to the load. Consequently, this leads to a significant reduction in the Total Voltage Blocking, standardization of the power semiconductors, and converter modularity structure. Furthermore, the proposed inverter topology presents voltage self-balancing capability, eliminating any balancing issues for the two floating capacitors of each voltage source inverter. The theoretical assumptions put forward in this study will be tested through experimental results obtained from a laboratory prototype.